Paisagem e manejo agrícola sustentável : influência na percepção, nos polinizadores e na produção de maracujá-amarelo (Passiflora edulis f. flavicarpa Deneger) - Silva, Jéssica Aretz Cunha Rodrigues da (2023)
Agriculture is one of the main economic sources in Brazil, with exports being fundamental to the economy. However, he cannot fail to highlight the importance of family farming, as it is from this segment that Brazilians obtain their food. To have high productivity and quality products, agricultural spaces depend on a healthy environment. In addition to this prominent social role, it is important to understand the perception of family farmers regarding ecosystem services. The general objective of this research is to evaluate the effect of the landscape on the availability of passion fruit pollinators and the environmental perception of these farmers. The collections were carried out in the Settlement Oiteiro de Miranda, located in the municipality of Lucena, North Coast of Paraíba. At each collection point, 5 buffers were arranged at different distances, where land use and land cover classification were performed for multiscale analysis. The individual-focal method was used to identify the pollinators. The fruits were evaluated according to their physical characteristics and the value of soluble solids content (°Brix) and a statistical regression analysis between physical characteristics and the abundance of pollinators. The results of the landscape effect show that the exposed soil hurts the species richness in 100m and 250m, showing that this class can negatively affect the availability and acquisition of resources for pollinating or robbing species. As for the fruits, the physical characteristics are very similar, with differences only in the number of seeds. Thus, it is of fundamental importance that there be a greater number of areas covered. Regarding the farmers' perception, we conducted semi-structured interviews with settlers over 18 years of age and the qualitative data was analyzed using the Quanteda package, from R. As for the farmers' perception, there was no significance in the relationship between schooling and the number of perceived services, nor the relationship between genders. However, with the relationship between the categories of ecosystem services and gender, there was a significant result for Support services. The analyzes did not corroborate our hypothesis, except the support service, however, the answers obtained through the interviews were fundamental for understanding the view of these workers on social and environmental aspects and how they see themselves affected by the environment that surrounds them.